2020
DOI: 10.3390/jcdd7030031
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Expression Profiles of β-Catenin during Murine Cardiac Valve Development

Abstract: β-catenin has been widely studied in many animal and organ systems across evolution, and gain or loss of function has been linked to a number of human diseases. Yet fundamental knowledge regarding its protein expression and localization remains poorly described. Thus, we sought to define whether there was a temporal and cell-specific regulation of β-catenin activities that correlate with distinct cardiac morphological events. Our findings indicate that activated nuclear β-catenin is primarily evident early in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Enhanced Wnt/β‐catenin signaling has been observed in human myxomatous valves 27‐29 . Hyperactivated β‐catenin can promote endothelial‐to‐mesenchyme transformation (EMT), endocardial proliferation, ECM remodeling and myxomatous degeneration of valves 30‐32 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Enhanced Wnt/β‐catenin signaling has been observed in human myxomatous valves 27‐29 . Hyperactivated β‐catenin can promote endothelial‐to‐mesenchyme transformation (EMT), endocardial proliferation, ECM remodeling and myxomatous degeneration of valves 30‐32 .…”
Section: Resultsmentioning
confidence: 99%
“…Enhanced Wnt/β‐catenin signaling has been observed in human myxomatous valves. 27 , 28 , 29 Hyperactivated β‐catenin can promote endothelial‐to‐mesenchyme transformation (EMT), endocardial proliferation, ECM remodeling and myxomatous degeneration of valves. 30 , 31 , 32 In this study as well as our previous reports on Dzip1 mutations, we observe similar findings of increased β‐catenin activities within the valves during development in a model ( Dzip1 S14R/+ ) that was previously validated as having myxomatous valves and MVP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(28) However, recent studies showed a discrepancy between the LEF1 and β-catenin expression in mouse embryonic heart valves, indicating that the pro-growth role of LEF1 is independent of β-catenin. (29) Here we found an extensive co-expression of LEF1 and YAP during valve remodeling. At E14.5, more than 75% of YAP expressing VIC also expressed LEF1 in both AV and OFT SL valves (Figure 2B).…”
Section: Resultsmentioning
confidence: 58%
“…The expressions of signaling programs during fetal valve remodeling are spatially and temporally regulated. 10,17,21,22 However, due to current difficulties with genetic models in studying these programs, neither the mechanisms of spatial and temporal regulations of the programs nor the environmental cues that govern them are well known. Genetic manipulation allows for the inference of the role of a gene by their global or lineagespecific absence from a tissue, which is challenging in a heterogeneously populated tissue-like valves.…”
Section: Introductionmentioning
confidence: 99%